PERSEPSI TUBUH DAN GANGGUAN MAKAN PADA REMAJA PEREMPUAN - Kurniawan, Mohamad Yulianto; Briawan, Dodik (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2014)
The objective of this study was to determine the relationship of body image perception and eating disorders in female adolescents. The design was a cross sectional study applied in new under graduate students majoring in nutritional sciences at Bogor Agricultural University (IPB) involving 103 female students. The results showed that the subjects proportion in normal nutritional status was 84.5%, overweight 11.7%, obesity 1.9%, and thin 1.9%. Most of the subjects tend to have more positive body perception (48.5%) which consisted of 44.7% without eating disorders and 3.9% had eating disorders. There was only 3.9% subject had a negative perception and 7.8% subject had eating disorders with more risk such as desiring to eat continously and could not stop eating 2—3 times a month. There was no significant correlation between body image perception with eating disorders (p>0.05).